Fabrication of Bi-Doped TiO2 Spheres with Ultrasonic Spray Pyrolysis and Investigation of Their Visible-Light Photocatalytic Properties. (5th June 2012) - Huang, Jianhui; Cheuk, Wahkit; Wu, Yifan; Lee, Frank S. C.; Ho, Wingkei
Abstract : Bismuth-doped TiO2 submicrospheres were synthesized by ultrasonic spray pyrolysis. The prepared bismuth-doped titania was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-visible diffuse reflectance spectroscopy (UV-vis DRS), and X-ray photoelectron spectroscopy (XPS). Aqueous photocatalytic activity was evaluated by the decomposition of methyl orange under visible-light irradiation. The results indicate that doping of bismuth remarkably affects the phase composition, crystal structure, and the photocatalytic activity. The sample with 2% Bi exhibits the optimum photocatalytic activity.